2016
DOI: 10.1016/j.geothermics.2016.02.004
|View full text |Cite
|
Sign up to set email alerts
|

The thermal structure and temporal evolution of high-enthalpy geothermal systems

Abstract: a b s t r a c tNumerical modeling is a powerful tool to investigate the response of high-enthalpy geothermal systems to production, yet few studies have examined the long-term evolution and thermal structure of these systems. Here we report a series of numerical simulations of fluid flow and heat transfer around magmatic intrusions which reveal key features of the natural thermal and hydraulic structures of high-enthalpy geothermal systems. We explore the effect of key geologic controls, such as host rock perm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
34
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 52 publications
(36 citation statements)
references
References 55 publications
2
34
0
Order By: Relevance
“…The simulations describe the development of a saline geothermal system within a two‐dimensional vertical section above a magmatic body intruded into host rocks with a permeability of 10 −15 m 2 initially containing pore waters with seawater salinity. We choose this permeability value because previous studies have shown that it is common in natural systems [ Björnsson and Bödvarsson , ; Manning and Ingebritsen , ] and close to optimal for the formation of spatially extensive supercritical geothermal resources in pure water systems [ Scott et al ., , ]. We performed simulations testing possible conditions for the Reykjanes system, in which intrusion depth and brittle‐ductile transition temperature are treated as variables.…”
Section: Methodsmentioning
confidence: 99%
“…The simulations describe the development of a saline geothermal system within a two‐dimensional vertical section above a magmatic body intruded into host rocks with a permeability of 10 −15 m 2 initially containing pore waters with seawater salinity. We choose this permeability value because previous studies have shown that it is common in natural systems [ Björnsson and Bödvarsson , ; Manning and Ingebritsen , ] and close to optimal for the formation of spatially extensive supercritical geothermal resources in pure water systems [ Scott et al ., , ]. We performed simulations testing possible conditions for the Reykjanes system, in which intrusion depth and brittle‐ductile transition temperature are treated as variables.…”
Section: Methodsmentioning
confidence: 99%
“…Scott et al (2015a, b) applied this modeling approach to evaluate processes in the supercritical zone in the IDDP-1 well. Scott et al (2016) modeled the temporal evolution of high enthalpy geothermal systems associated with shallow intrusions, and observed that host rock permeability and composition, intrusion depth, intrusion geometry, and strain rate all play important roles in the thermal structure. Scott et al (2017) noted that, for saline hydrothermal systems, the depth of the magmatic intrusions powering geothermal systems impacts the efficiency of heat transfer.…”
Section: Conceptual Models and Numerical Simulation Studiesmentioning
confidence: 99%
“…Here we will refer to this state as a young system. The temperature-depth profile of such a young system is reproduced from Scott et al (2016) in blue in Figure 8a. At later times, fluid convection involves larger and larger parts of the system, up to the point where the upflowing fluid is no longer hindered by the cold and dense overlying liquid groundwater and a boiling zone is established from large depths up to the surface.…”
Section: Geothermal Reservoir Modelmentioning
confidence: 99%